2012
DOI: 10.1210/en.2011-1882
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hypothalamic Proopiomelanocortin Neuron Autophagy in the Control of Appetite and Leptin Response

Abstract: Autophagy is a catabolic cellular process involving the degradation of the cell's own components. Although the role of autophagy of diverse tissues in body metabolism has been investigated, the importance of autophagy in hypothalamic proopiomelanocortin (POMC) neurons, key regulators of energy balance, has not been addressed. The role of autophagy in leptin sensitivity that is critical for the control of body weight and appetite has also not been investigated. We produced mice with specific deletion of autopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(115 citation statements)
references
References 36 publications
4
106
1
4
Order By: Relevance
“…Autophagy knockout in adipose tissue also leads to protection from diet-induced obesity and insulin resistance together with impaired adipocyte differentiation 7,9 . Autophagy deficiency in hypothalamic proopiomelanocortin neurons leads to obesity and glucose intolerance [47][48][49] . In addition to the location of autophagy deficiency, severity of autophagy deficiency could also be important.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy knockout in adipose tissue also leads to protection from diet-induced obesity and insulin resistance together with impaired adipocyte differentiation 7,9 . Autophagy deficiency in hypothalamic proopiomelanocortin neurons leads to obesity and glucose intolerance [47][48][49] . In addition to the location of autophagy deficiency, severity of autophagy deficiency could also be important.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated that Atg7 deletion in POMC neurons causes increased body weight owing to hyperphagia [87][88][89] . However, more recent research argues against a general role for POMC neuron-specific autophagy in the control of energy homeostasis.…”
Section: Danon Diseasementioning
confidence: 99%
“…RNA from paraffin-embedded tissue blocks was prepared using a formalin-fixed paraffin-embedded kit (Qiagen, 56404). cDNA was synthesized using M-MLV reverse transcriptase (Promega, M17013) and oligo(dT) [12][13][14][15][16][17][18] primer. The expression of Atg7, Tnf, Il6, pro-Il1b, Adgre1, Tgfb, Ccl2, Ccl5, Cxcl1 and Actb was assessed by quantitative PCR using specific primer sets.…”
Section: Rt-pcrmentioning
confidence: 99%
“…11,12 As these results suggest that autophagy deficiency is a proinflammatory condition particularly in relation to inflammasome activation, deficient autophagy can be a factor in the development of T2D associated with low-grade inflammation and inflammasome activation. Although the role of autophagy of diverse tissues in body metabolism has been intensively investigated, [13][14][15][16][17][18][19][20][21] the importance of autophagy of myeloid cells such as Mfs (macrophages) in the regulation of systemic insulin sensitivity and in the development of T2D has not been clearly elucidated. Besides metabolic syndrome, IBD (inflammatory bowel disease) is a prototypic disease associated with autophagy deficiency inducing aggravated tissue inflammation.…”
Section: Introductionmentioning
confidence: 99%